An Examination of the Palladium/Mor‐DalPhos Catalyst System in the Context of Selective Ammonia Monoarylation at Room Temperature1. Issue 6 (4th January 2013) - Alsabeh, Pamela G.; Lundgren, Rylan J.; McDonald, Robert; Johansson Seechurn, Carin C. C.; Colacot, Thomas J.; Stradiotto, Mark
Abstract An examination of the [{Pd(cinnamyl)Cl}2]/Mor‐DalPhos (Mor‐DalPhos=di(1‐adamantyl)‐2‐morpholinophenylphosphine) catalyst system in Buchwald–Hartwig aminations employing ammonia was conducted to better understand the catalyst formation process and to guide the development of precatalysts for otherwise challenging room‐temperature ammonia monoarylations. The combination of [{Pd(cinnamyl)Cl}2] and Mor‐DalPhos afforded [(κ2‐P, N‐Mor‐DalPhos)Pd(η1‐cinnamyl)Cl] (2), which, in the presence of a base and chlorobenzene, generated [(κ2‐P, N‐Mor‐DalPhos)Pd(Ph)Cl] (1 a). Halide abstraction from 1 a afforded [(κ3‐P, N, O‐Mor‐DalPhos)Pd(Ph)]OTf (5), bringing to light a potential stabilizing interaction that is offered by Mor‐DalPhos. An examination of [(κ2‐P, N‐Mor‐DalPhos)Pd(aryl)Cl] (1 b–f) and related precatalysts for the coupling of ammonia and chlorobenzene at room temperature established the suitability of 1 a in such challenging applications. The scope of reactivity for the use of 1 a (5 mol %) encompassed a range of (hetero)aryl (pseudo)halides (X=Cl, Br, I, OTs) with diverse substituents (alkyl, aryl, ether, thioether, ketone, amine, fluoro, trifluoromethyl, and nitrile), including chemoselective arylations.